2016
DOI: 10.15376/biores.11.2.4850-4864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acid Copper Chromate Preservative and Hydrothermal Treatment on the Dimensional Stability, Hardness, and Decay Resistance of Poplar Wood

Abstract: The effects of acid copper chromate (ACC) and hydrothermal treatments were determined relative to the hardness, decay resistance, and dimensional stability of poplar wood. Test specimens, prepared from poplar wood (Populus nigra L.), were first heat-treated under saturated steam in a digester and then impregnated with ACC solution and by a long-term (21 days) dipping technique to reach complete saturation. Impregnated specimens were exposed to white-rot fungus (Trametes versicolor) for 14 weeks, using the Koll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Militz [ 84 ] reported an increase in resistance against Hylotrupes bajulus , Lyctus brunneus , and Anobium punctatum for heat-treated wood. Hadi et al [ 85 ] conducted a study on the effects of hydrothermal modification of modified poplar wood treated with acid–copper–chromate at various concentrations. They found that the improved decay-resistance properties of wood depended on the treatment temperature and time.…”
Section: Effects Of Hydrothermal Modification On Wood Propertiesmentioning
confidence: 99%
“…Militz [ 84 ] reported an increase in resistance against Hylotrupes bajulus , Lyctus brunneus , and Anobium punctatum for heat-treated wood. Hadi et al [ 85 ] conducted a study on the effects of hydrothermal modification of modified poplar wood treated with acid–copper–chromate at various concentrations. They found that the improved decay-resistance properties of wood depended on the treatment temperature and time.…”
Section: Effects Of Hydrothermal Modification On Wood Propertiesmentioning
confidence: 99%